Faktor-Faktor yang Mempengaruhi Volume Penjualan Pada Toko Delta Convection, Pedan, Klaten - Iin Emy Prastiwi; Abdul Haris Romdhoni; Yuliana Rikha Widayati (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
This study aims to examine and analyze the effect of product quality and Islamic marketing on sales volume to consumers at the Delta Convection Pedan Klaten store. This study uses a quantitative descriptive approach. The technique collected is in the form of primary data through a questionnaire distributed to respondents called a questionnaire. the data collection technique used purposive sampling technique, namely the technique of determining the sample with certain considerations, namely using certain criteria such as consumer purchase data in 2019 to 2020, this research was carried out by distributing questionnaires and carried out by 76 consumers from 310 consumers at the Delta Multi Convection store. from the results of the study that the product quality variable had no significant effect from the results of the study that the product quality variable had no significant effect on sales volume from the results of the study that the product quality variable had no significant effect on sales volume. It is obtained equally from the research results that the product quality variable has no significant effect on sales volume, namely the results obtained calculated = 1.931 which from the research results that the product quality variable has no significant effect on sales volume, namely the results obtained calculated = 1.931 which means t count < t table (1,931 <1.992) and sig t = 0.057 > 0.05, then Ho is accepted and Ha is rejected. Sharia marketing variables have a significant effect on sales volume, namely the results obtained t count = 6.454 which means t count > from t table (6.454 > 1.992) and sig t = 0.000 <0.05, then Ho is rejected and Ha is accepted. product quality and sharia marketing have a simultaneous effect on sales volume.